Study on the Granting of Marriage License to Civil Servants - Sri Hariati; Haeratun (PT FORMOSA CENDEKIA GLOBAL, 2023)
Marriage is a very important institution in society. The existence of the institution is to legalize the legal relationship between a man and a woman. Marriage, according to Law Number 1 of 1974 Concerning Marriage and Islamic Law, not only seen from a purely formal aspect, but also from a religious and social aspect. In the religious aspect to determine the validity of marriage, while the formal aspect is related to administrative aspects, namely registration at the Office of Religious Affairs and civil registration. In the conception of Western civil law, marriage is seen in civil relations only. It means that the law does not interfere in ceremonies held by the church. The law only concerns